2021
DOI: 10.1101/2021.12.08.471760
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geographic variation in larval cold tolerance and exposure across the invasion front of a widely established forest insect

Abstract: As the global climate changes, high and low temperature extremes can drive changes in species distributions. Across the range of a species, thermal tolerance can experience plasticity and may undergo selection, shaping resilience to temperature stress. In this study, we measured variation in the lower thermal tolerance of early instar larvae of an invasive forest insect, Lymantria dispar dispar L. (Lepidoptera: Erebidae), using populations sourced from the climatically diverse invasion of the Eastern United St… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In models that predict potential distributions of invasive species, there is increasing recognition that increasing complexity does not always translate into an increase in model performance (Gallien et al, 2010). Although we chose variables to represent long-distance transport and developmental performance that were grounded in prior research (Gray, 2009;Hafker et al, 2021;Thompson, Powers, et al, 2021;Walter, Johnson, et al, 2015), it is possible that other representations of these mechanisms, or of other mechanisms We also found that forecast accuracy tended to be highest for lower occupancy thresholds and shorter Omniscape radii. One possible explanation for the stronger performance of models using shorter Omniscape radii is the short spatial scale of natural dispersal by L. dispar.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In models that predict potential distributions of invasive species, there is increasing recognition that increasing complexity does not always translate into an increase in model performance (Gallien et al, 2010). Although we chose variables to represent long-distance transport and developmental performance that were grounded in prior research (Gray, 2009;Hafker et al, 2021;Thompson, Powers, et al, 2021;Walter, Johnson, et al, 2015), it is possible that other representations of these mechanisms, or of other mechanisms We also found that forecast accuracy tended to be highest for lower occupancy thresholds and shorter Omniscape radii. One possible explanation for the stronger performance of models using shorter Omniscape radii is the short spatial scale of natural dispersal by L. dispar.…”
Section: Discussionmentioning
confidence: 99%
“…We represented the temperature‐dependent developmental performance of L. dispar in each grid cell for each year by combining gridded climate data (Thornton et al., 2020) with three measures of physiological performance: (1) a numerical model of temperature‐dependent growth and development (Gray, 2004, 2009); (2) cold exposure risk based on experimental data on cold tolerance (Hafker et al., 2021); and (3) the pupal mass of L. dispar reared in different thermal environments (Thompson, Powers, et al., 2021). Because previous studies provide evidence of local adaptation in L. dispar responses to temperature (Faske et al., 2019; Hafker et al., 2021; Thompson et al., 2017; Thompson, Powers, et al., 2021), we incorporated this variation into the second and third components of developmental performance. In the first component, the model of Gray (2009) was used to evaluate whether a typical individual would complete its life stage in a given year (See details in Data S1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations